How Well Do Catholic and Other Faith-based Schools Serve the Poor? A Study with Special Reference to Africa : Part II -- Learning - Wodon, Quentin (Taylor and Francis, 2020)
This paper is the second in a set of two on the extent to which Catholic and other faith-based schools are serving the poor well. Catholic and other faith-based schools reach millions of children who live in poverty, yet this does not necessarily mean that they are serving these children well enough. The paper considers two separate issues. First, beyond academic subjects, Catholic and other faith-based schools emphasize learning related to values and religion. Do they succeed in doing so? Based on small sample survey data and qualitative fieldwork, as well as broader data on parental satisfaction with schools, the paper provides a tentative and mostly positive answer to this question, at least from the view of parents. The second issue is where performance is weaker. Education systems are affected by a learning crisis in the developing world. All schools should ensure that students learn, but too often this is not the case. The second part of the paper documents this learning crisis and the fact that Catholic and other faith-based schools are not immune to it. This is done in part through a rapid review of the recent World Development Report on education's promise, and a companion piece for sub-Saharan Africa. Estimates of performance for selected African countries are also provided. The results are sobering: too many children are not learning while in school. Finally, the paper briefly summarizes evidence from the literature on interventions that could improve learning, including in Catholic and faith-based schools.